P25 Stroke risk from atrial fibrillation in repaired tetralogy of fallot. (2nd March 2016) - Moore, Heather; Abiodun, Aderonke; Bowater, Sarah; Clift, Paul; Thorne, Sara; Bono, Joseph De; Hudsmith, Lucy
Abstract : Background: Atrial fibrillation (AF) has a prevalence of 1.6% in the UK and significantly increases the risk of developing a stroke. Adults with congenital heart disease have an increased risk of developing arrhythmias, a leading cause of morbidity and mortality in these patients. CHADSVASC scoring system is a recommended tool for assessing thromboembolic risk in AF for the general population; its role in adult congenital heart disease is still uncertain. Method: All patients with repaired Tetralogy of Fallot (TOF) and atrial fibrillation were identified from our database and their notes were retrospectively reviewed. Results: 35 of the 456 (7.7%) patients with repaired TOF under regular follow-up at a large quaternary Specialist Adult Congenital Disease Centre were identified as having AF, mean age 56.5(+/-12.1) years, range 27–77 years, 19 male (54.3%). The average CHADSVASC score was 1.83 (range 0–4). Most were anticoagulated; 28 (80%) received warfarin, 3 (8.6%) took a novel anticoagulant (NOAC) but 4 patients were not anticoagulated. The mean age of initial AF diagnosis was 48(+/-13.7) years. 15 (42.9%) patients were diagnosed with AF before the age of 45 years and 7 (20%) before the age of 35 years. Most patients were symptomatic. 5 (14.3%) patients had either a stroke or a transient ischaemic attack. 2 had multiple strokes. 3 of the patients had strokes when they had known AF but were not anticoagulated having CHADVASC scores of 2 or less. 1 patient had 2 strokes in their twenties but was not diagnosed with AF until their 40s. 1 patient suffered a stroke while prescribed rivaroxaban. Conclusion: The risk of stroke in TOF appears high. It is unclear whether the CHADSVASC score is useful for risk stratification. This data suggest that anticoagulation should be considered in all patients with TOF and AF, irrespective of CHADSVASC score. The role of NOACs in this population is unclear.